The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1519/jsc.0000000000000285
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Reliability of GPS Devices for Measurement of Sports-Specific Movement Patterns Related to Cricket, Tennis, and Field-Based Team Sports

Abstract: The aim of this study was to determine the accuracy and reliability of 5, 10, and 15 Hz global positioning system (GPS) devices. Two male subjects (mean ± SD; age, 25.5 ± 0.7 years; height, 1.75 ± 0.01 m; body mass, 74 ± 5.7 kg) completed 10 repetitions of drills replicating movements typical of tennis, cricket, and field-based (football) sports. All movements were completed wearing two 5 and 10 Hz MinimaxX and 2 GPS-Sports 15 Hz GPS devices in a specially designed harness. Criterion movement data for distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 18 publications
6
91
1
Order By: Relevance
“…The reliability of GPS has been demonstrated to rise proportionally with displacement distance (Coutts & Duffield, 2010;Petersen, Pyne, Portus, & Dawson, 2009). Vickery et al (2014) found no horizontal dilution of positioning using 15 Hz devices, unlike the results obtained with 5-10 Hz versions. The validity of the instrument closely depends on sampling frequency, the speed and the duration of the task (Aughey, 2011).…”
Section: Introductioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The reliability of GPS has been demonstrated to rise proportionally with displacement distance (Coutts & Duffield, 2010;Petersen, Pyne, Portus, & Dawson, 2009). Vickery et al (2014) found no horizontal dilution of positioning using 15 Hz devices, unlike the results obtained with 5-10 Hz versions. The validity of the instrument closely depends on sampling frequency, the speed and the duration of the task (Aughey, 2011).…”
Section: Introductioncontrasting
confidence: 55%
“…The only criterion adopted was that subjects wore the same device during the match on the red clay and the hard court. Indeed, due to lower inter-unit reliability it is advisable that athletes use the same device within any research design in order to avoid inter-unit errors Vickery et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…No other parameters were taken into account in this study (Vickery et al, 2014) due to gold-standard data recommendation (Cummins et al, 2013)…”
Section: Methodsmentioning
confidence: 99%
“…12,14,15 While these studies provided a thorough assessment of velocity, acceleration, and deceleration compared with high-sampling criterion measures, the limitations were that they did not assess using sport-specific movements involving changes in direction. Other studies have employed sport-specific movement circuits, 8,11,[16][17][18][19] however most of these studies are limited in the criterion measures used to evaluate velocity (eg, timing gates, 20,21 ) and synchronization protocols are not well documented.…”
Section: Reliability and Validity Of Commercial Gps Devicesmentioning
confidence: 99%